[PP.23.02] RESISTANT HYPERTENSION AND RENAL RESISTIVE INDEX. (September 2016) - Tandurella, N.; Tavecchia, L.; Agostinis, M.; Mongiardi, C.; Gadaleta, C.; Moretti, S.; Test, L. Robustelli; Grossi, A.; Pierobon, V.; Maresca, A.M.; Guasti, L.; Grandi, A.M.
Abstract : Objective: Renal resistive index (RRI), assessed by Doppler sonography, has been classically considered as an expression of intrarenal vascular resistance. Recent studies, however, have showed that RRI is also influenced by arterial compliance, confirming its possible role as a marker of systemic vascular alterations. Our purpose was the evaluation of the renal resistive index in patients with uncontrolled hypertension with 3 or more antihypertensive drugs, including a diuretic (RH), in comparison with a group of patients with resistant drug hypertension controlled with 4 or more antihypertensive drugs (RH4) and patients with hypertension controlled with 3 antihypertensive agents (CH3). We also considered the correlation between renal resistive index and subclinical organ damage. Design and method: We enrolled 120 patients (40 RH, 40 RH4, 40 CH3) without renal arterial stenosis and known nephropathy from our outpatient clinic for hypertension. We matched patients for age, sex and BMI. Each patients performed a 24-hour blood pressure monitoring (ABPM), office blood pressure (OBP) measurement, Glomerular Filtration Rate (according to MDRD) assessment, echocardiography and carotid echo-color-Doppler ultrasonography. We also estimated renal resistive index by Doppler sonography. Results: OBP and ABP were higher in RH group in comparison with the RH4 and CH3 groups (OBP: 155 ± 7/88 ± 5 vs 130 ± 7/79 ± 9 vs 127 ± 7/76 ± 5 mmHg, p = 0.001; ABP: 141 ± 10/85 ± 6 vs 122 ± 8/73 ± 6 vs 121 ± 8/72 ± 6 mmHg, p = 0.001). Office pulse pressure was higher in RH than RH4 and CH3 groups (66 ± 12 vs 53 ± 10 vs 51 ± 6 mmHg, p = 0.001). Renal resistive index was similar in RH and RH4 (0.72 ± 0.08 vs 0.70 ± 0.07, p = n.s.) and higher than CH3 group (0.72 ± 0.08 vs 0.65 ± 0.06, p = 0.004; 0.70 ± 0.07 vs 0.65 ± 0.06, p = 0.019). We also found a significant correlation between renal resistive index and age (r = 0.421, p = 0.0001), GFR (r = −0.197, p = 0.036), office pulse pressure (r = 0.4 p = 0.0001). We did not observe significant correlation between renal resistive index and left ventricular mass index and carotid intima-media thickness. Conclusions: Renal resistive index is higher in patients with drug-resistant hypertension. The correlation between office pulse pressure and the renal resistive index confirms that the latter depends much more on systemic haemodynamics than on renal ones. These data need to be confirmed by larger and prospective studies.